Withering away of cartesian dichotomies: the theses on feuerbach and praxis as an epistemological kategory - Kaya, Evrim. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2013., 2013)
The main project of the thesis is to explain the notion of praxis as formulated by Karl Marx as an answer to the distinctively Cartesian problem of the relation between the subject and the object. Focusing mainly on the early writings of Marx and with a special consideration of the eleven thesis directed at Feuerbach, I try to shad light on the Kantian -‐ Hegelian roots of the notion as a unifying category between theory and practice and reformulate it as an epistemological category following the path provided by constructivist philosophies going back to Kant, where the mind plays an active role. For that matter, in the first chapters, the problem is presented in its Cartesian and modernist core and three reactions from three different historical viewpoints are summarized: from a so-‐called naïve, pre-‐modern metaphysics where mind is passive yet no doubt about knowledge is raised, from the tradition of empiricism where experience is the ultimate limit of knowledge and from critical philosophies starting with Kant and continuing with Hegel to Marx. Through a reading of Theses ad Feuerbach, a Marxist answer residing in the category of praxis is formulated in which different views from idealist and materialist tradition are combined in search for a constructivist materialism.